Comprehensive Physiology 2017
DOI: 10.1002/cphy.c160042
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity and Metabolic Health: Harmony Becomes Dissonant in Obesity and Aging

Abstract: Adipose tissue (AT) is the primary energy reservoir organ, and thereby plays a critical role in energy homeostasis and regulation of metabolism. AT expands in response to chronic overnutrition or aging and becomes a major source of inflammation that has marked influence on systemic metabolism. The chronic, sterile inflammation that occurs in the AT during the development of obesity or in aging contributes to onset of devastating diseases such as insulin resistance, diabetes, and cardiovascular pathologies. Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 279 publications
0
13
0
Order By: Relevance
“…Mice fed with a high level of fats and carbohydrates have been widely used and provided important clues in the interrelated pathology of obesity, inflammation and metabolic diseases [6, 19, 20]. Interestingly, diet- and senescence-induced obesity share many aspects of pathogenesis, which are collectively presented in two recent detailed reviews [57, 58]. One important commonality is that energy-rich diets cause a subclinical, chronic, low-grade systemic inflammatory state, which is similar to what is caused by immunosenescence in both aged animals and humans [57, 58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice fed with a high level of fats and carbohydrates have been widely used and provided important clues in the interrelated pathology of obesity, inflammation and metabolic diseases [6, 19, 20]. Interestingly, diet- and senescence-induced obesity share many aspects of pathogenesis, which are collectively presented in two recent detailed reviews [57, 58]. One important commonality is that energy-rich diets cause a subclinical, chronic, low-grade systemic inflammatory state, which is similar to what is caused by immunosenescence in both aged animals and humans [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, diet- and senescence-induced obesity share many aspects of pathogenesis, which are collectively presented in two recent detailed reviews [57, 58]. One important commonality is that energy-rich diets cause a subclinical, chronic, low-grade systemic inflammatory state, which is similar to what is caused by immunosenescence in both aged animals and humans [57, 58]. In our previous line of research using probiotic bacteria to counteract the deleterious effects of a Western-style obesogenic diet in mice, we observed mice consuming the high-fat diet had a dramatic decrease in the populations of Tregs in mesenteric [8] and mammary lymph nodes [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose tissue expansion with age is also thought of as a major source of inflammation that has a marked influence on systemic metabolism and contributes to the onset of devastating conditions such as insulin resistance, type-2 diabetes, and cardiovascular disorders [ 13 ]. However, during the development of diet-induced obesity or age-associated adiposity, immunocompetent cells infiltrate and proliferate in the adipose tissue.…”
Section: Contributing Factors To Immune Declinementioning
confidence: 99%
“…It has been suggested that anti-inflammatory properties of exercise depend on two key mechanisms. First, regular exercise reduces visceral fat mass, a major source of inflammation, also known as “metflammation” (indirect effect) [16, 17]. Second, regular exercise and higher physical fitness levels are associated with increased numbers and proportions of circulating anti-inflammatory regulatory T-cells (T regs ) (direct effect) [18].…”
Section: Introductionmentioning
confidence: 99%